Almost Periodic Synchronization for Quaternion-Valued Neural Networks with Time-Varying Delays. (29th April 2018) - Li, Yongkun; Meng, Xiaofang; Ye, Yuan
Abstract : This paper focuses on the global exponential almost periodic synchronization of quaternion-valued neural networks with time-varying delays. By virtue of the exponential dichotomy of linear differential equations, Banach's fixed point theorem, Lyapunov functional method, and differential inequality technique, some sufficient conditions are established for assuring the existence and global exponential synchronization of almost periodic solutions of the delayed quaternion-valued neural networks, which are completely new. Finally, we give one example with simulation to show the applicability and effectiveness of our main results.